2021
DOI: 10.1002/chem.202004045
|View full text |Cite
|
Sign up to set email alerts
|

π–π Catalysis in Carbon Flatland—Flipping [8]Annulene on Graphene

Abstract: Noncovalent interactions are an integral part of the modern catalysis toolbox. Although stronger noncovalent interactions such as hydrogen bonding are commonly the main driving force of catalysis, π–π interactions typically provide smaller additional stabilizations, for example, to afford selectivity enhancements. Here, it is shown computationally that pristine graphene flakes may efficiently catalyze the skeletal inversions of various benzannulated cyclooctatetraene derivatives, providing an example of a cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 81 publications
0
16
1
Order By: Relevance
“…It is important to emphasize that both the free and adsorbed planar COT structures are first-order saddle points possessing an imaginary frequency that corresponds to the tub-inversion. 44 In contrast, in the current work we find that the planar structure of para dibenzannulated COT adsorbed on graphene is no longer a first-order saddle point, but a local minimum with all-real frequencies (the optimized structure of the equilibrium complex is depicted in Figure 5). Thus, it seems that in the case of DBCOT, the graphene monolayer reshapes the PES such that the TS for the tub-inversion becomes a local minimum.…”
Section: Structure Of Dbcot Adsorbed On a Graphene Nanoflakecontrasting
confidence: 79%
See 4 more Smart Citations
“…It is important to emphasize that both the free and adsorbed planar COT structures are first-order saddle points possessing an imaginary frequency that corresponds to the tub-inversion. 44 In contrast, in the current work we find that the planar structure of para dibenzannulated COT adsorbed on graphene is no longer a first-order saddle point, but a local minimum with all-real frequencies (the optimized structure of the equilibrium complex is depicted in Figure 5). Thus, it seems that in the case of DBCOT, the graphene monolayer reshapes the PES such that the TS for the tub-inversion becomes a local minimum.…”
Section: Structure Of Dbcot Adsorbed On a Graphene Nanoflakecontrasting
confidence: 79%
“…We recently found that adsorption of COT onto a graphene nanoflake catalyst (C 96 H 24 ) reduces its ring inversion barrier height by 20% of the uncatalyzed reaction barrier height. 44 Structural and energetic analyses show that this catalytic activity is driven by shape complementarity between the planar 2D catalyst and planar TS. Namely, the 2D nanomaterial stabilizes the planar TS to a greater extent than the highly nonplanar, tub-shaped reactant.…”
Section: Structure Of Dbcot Adsorbed On a Graphene Nanoflakementioning
confidence: 99%
See 3 more Smart Citations